ATM Shield: Analysis of Multitier Security Issues of ATM in the Context of Bangladesh - Rumman, Md. Raqibul Hasan; Sarker, Atish; Islam, Md. Majharul; Hoque, Md. Imdadul; Kuri, Robin; Bhuyan, Md. Babar Ali; Bhuiyan, Nayeem Al-Tamzid (Journal of Experimental Sciences, 2020)
Over the last decade, consumers have been largely dependent on and trust the Automatic Teller Machine (ATM) to conveniently meet their banking needs. However, despite the numerous advantages of ATM system, ATM fraud has recently become more widespread. In this paper, we provide an overview of the possible fraudulent activities that may be perpetrated against ATMs and investigates recommended approaches to prevent these types of frauds. In particular, we develop a prototype model for the utilization of three tier security equipped ATM to provide security solutions against must of the well-known breaches. In this research article, the tools and techniques of ATM fraud are contemplated. A secure three layer electronic transaction mechanism of ATM is developed to prevent ATM frauds. In this three layer authentication systems the users can improve ATM security against frauds and crimes.